Geschichte des Sozialismus (Ullstein)
Von 1875 bis 1918. 8: Der Sozialismus in Amerika, Asien, Afrika / François Bédarida, Jean Chesneaux, Marianne Debouzy. - 1976. - 137 p. - (Ullstein Buch ; 3226). - Bibl., index. - ISBN 3-548-03226-5